Pattu meshari Canal (pa-at-tu me-šá-ri) and the possibility of matching it with the Abbasid River in light of the published cuneiform texts and The Archaeological surveys - Al-Hamedha, Ghassan (Al-Adab Journal, 2025)
The research is an attempt to shed light on the oldest Assyrian irrigation canal dating back to the Middle Assyrian era, specifically to the time of the reign of King Tukulti Ninurta I (1244-1208 BC), who dug it to irrigate the plain lands opposite the city of Assyria on the left side of the Tigris River, which is known to geographers nowadays as - “Makhmur Plain”, as well as irrigating the lands surrounding his new city of Kar-Tukulti-Ninurta and turning them into green meadows. This study relied on two important sources, the first on the cuneiform writings left by the king, especially those that talk about the founding of the city, as they always touch on the irrigation canal and the role of the king in constructing that canal, and that that canal is an important source for offering sacrifices from the revenues of that canal, especially since it turned barren lands into fields. It is irrigated and grows all kinds of crops, in addition to fish caught from the canal. The second source includes archaeological surveys and field surveys, including satellite images, in order to search and investigate the remains of that canal, which the locals currently call the Abbasid River, and an attempt to trace its path despite the passage of thousands of years since it was mentioned in the king’s writings, and to find out the possibility of matching it with What is mentioned in the cuneiform text.